Tuberculosis drug streptomycin as a potential cancer therapeutic: inhibition of miR-21 function by directly targeting its precursor - Bose, Debojit; Jayaraj, Gopal Gunanathan; Suryawanshi, Hemant; Agarwala, Prachi; Pore, Subrata Kumar; Banerjee, Rajkumar; Maiti, Souvik (Angewandte Chemie-International Edition, 2012)
Keywords: Apoptosis; drug discovery; Gene expression; inhibitors; RNA

Effect of loops and G-quartets on the stability of RNA G-quadruplexes - Pandey, Satyaprakash; Agarwala, Prachi; Maiti, Souvik (Journal of Physical Chemistry B, 2013)
The loop length, loop composition, salt concentration, and number of G-quartets are major determinants of G-quadruplex stability. We examined the effect of each of these factors on the thermal stability and folding topology of a library of RNA quadruplexes. The thermal stability of G2 and G3 RNA quadruplexes was investigated upon varying the loop length (from 1-1-1 to 15-15-15) and salt concentration (from sequence 1 to 100 mM KCl), while the effect of loop composition was explored using 18 naturally occurring potential RNA quadruplexes predicted in untranslated regions (UTRs). We found loop length and quadruplex stability to be inversely related for G2 RNA quadruplexes and G3 RNA quadruplexes with shorter loops. However, melting temperature saturates for G3 RNA quadruplexes with longer loops. RNA G-quadruplexes with longer loops (G3 15-15-15) displayed T-m values significantly higher than the physiological temperature. This study thus highlights the need to modify the consensus motif presently used by quadruplex prediction tools. An increase in the loop size from 7 bases to IS bases in the consensus motif will add to its predictive value for the discovery of potential RNA quadruplexes across transcriptomes.

G-quadruplex augments translation in the 5 ` untranslated region of transforming growth factor beta 2 - Agarwala, Prachi; Pandey, Satyaprakash; Mapa, Koyeli; Maiti, Souvik (Biochemistry, 2013)
Transforming growth factor beta 2 (TGF beta 2) is a versatile cytokine with a prominent role in cell migration, invasion, cellular development, and immunomodulation. TGF beta 2 promotes the malignancy of tumors by inducing epithelial-mesenchymal transition, angiogenesis, and immunosuppression. As it is well-documented that nucleic acid secondary structure can regulate gene expression, we assessed whether any secondary motif regulates its expression at the post-transcriptional level. Bioinformatics analysis predicts an existence of a 23-nucleotide putative G-quadruplex sequence (PG4) in the 5' untranslated region (UTR) of TGF beta 2 mRNA. The ability of this stretch of sequence to form a highly stable, intramolecular parallel quadruplex was demonstrated using ultraviolet and circular dichroism spectroscopy. Footprinting studies further validated its existence in the presence of a neighboring nucleotide sequence. Following structural characterization, we evaluated the biological relevance of this secondary motif using a dual luciferase assay. Although PG4 inhibits the expression of the reporter gene, its presence in the context of the entire 5' UTR sequence interestingly enhances gene expression. Mutation or removal of the G-quadruplex sequence from the 5' UTR of the gene diminished the level of expression of this gene at the translational level. Thus, here we highlight an activating role of the G-quadruplex in modulating gene expression of TGF beta 2 at the translational level and its potential to be used as a target for the development of therapeutics against cancer.

G-Quadruplexes as tools for synthetic biology - Agarwala, Prachi; Pandey, Satyaprakash; Maiti, Souvik (Chembiochem, 2013)
With the potential to engineer biological systems, synthetic biology is an emerging field that combines various disciplines of sciences. It encompasses combinations of DNA, RNA and protein modules for constructing desired systems and the rewiring of existing signalling networks. Despite recent advances, this field still lags behind in the artificial reconstruction of cellular processes, and thus demands new modules and switches to create genetic circuits. The widely characterised noncanonical nucleic acid secondary structures, G-quadruplexes are promising candidates to be used as biological modules in synthetic biology. Structural plasticity and functional versatility are significant G-quadruplex traits for its integration into a biological system and for diverse applications in synthetic circuits.
Keywords: G-quadruplexes; ribozymes; synthetic biology; topology; zipcodes

Role of G-quadruplex located at 5 end of mRNAs - Agarwala, Prachi; Pandey, Satyaprakash; Maiti, Souvik (Biochimica Et Biophysica Acta-General Subjects, 2014)
Background: Secondary structures in 5' UTR of mRNAs play a critical role in regulating protein synthesis. Though studies have indicated the role of secondary structure G-quadruplex in translational regulation, position-specific effect of G-quadruplex in naturally occurring mRNAs is still not understood. As a pre-initiation complex recognises 5' cap of the mRNA and scans along the untranslated region (UTR) before initiating translation, the presence of G-quadruplex in 5' region may have a significant contribution in regulating translation. Here, we investigate the role of G-quadruplex located at the 5' end of an mRNA. Methods: Biophysical characterisation of putative G-quadruplexes was performed using UV and CD spectroscopy. Functional implication of G-quadruplex in the context of their location was assessed in cellulo using gRT-PCR and dual luciferase assay system. Results: PG4 sequences in 5' UTR of AICT interacting protein (AKTIP), cathepsin B (CTSB) and forkhead box E3 (FOXE3) mRNAs form G-quadruplex whereas it is unable to form G-quadruplex in apolipoprotein A-I binding protein (APOA1BP). Our results demonstrated diverse roles of G-quadruplex located at 5' end of mRNAs. Though G-quadruplex in AKTIP and CTSB mRNA act as inhibitory modules, it activates translation in FOXE3 mRNA. Conclusions: Our works suggests that G-quadruplex present at the 5' terminal of an mRNA behaves differently in a different gene context. It can activate or inhibit gene expression. General significance: This study demonstrated that it is difficult to predict the role of G-quadruplex on the basis of its position in 5' UTR. The neighbouring nucleotide sequence, the intracellular milieu and the interacting partners might render diverse functions to this secondary structure. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: AKTIP; APOA1BP; CTSB; FOXE3; G-quadruplex; UTR

Human telomeric RNA G-quadruplex response to point mutation in the G-quartets - Agarwala, Prachi; Kumar, Santosh; Pandey, Satyaprakash; Maiti, Souvik (Journal of Physical Chemistry B, 2015)
Many putative G-quadruplex forming sequences have been predicted to exist in the human genome and transcriptome. As these sequences are subject to point mutations or SNPs (single nucleotide polymorphisms) during the course of evolution, we attempt to understand impact of these mutations in context of RNA G-quadruplex formation using human telomeric RNA (TERRA) as a model sequence. Our studies suggest that G-quadruplex stability is sensitive to substitution of the guanines comprising G-quartets. While central G-quartet plays a crucial role in maintaining the DNA G-quadruplex stability as evident in literature, there is equal importance of three G-quartets in the stability of RNA quadruplex structure. The work here highlights the alterations in the G-quartet are detrimental to the integrity of overall RNA G-quadruplex structure. Furthermore, TmPyP4 molecules are shown to exhibit similar binding behavior toward telomeric RNA G-quadruplex harboring base substitutions employing CD titrations and isothermal titration calorimetry; well indicating that mutation does not influence TmPyP4 recognition ability as it affects the stability of RNA G-quadruplex. Thus, our study implicates that mutation in G-quartets causes destabilization of RNA G-quadruplex without affecting its trans factor binding ability.

RNA stem-loop to G-quadruplex equilibrium controls mature MicroRNA production inside the cell - Pandey, Satyaprakash; Agarwala, Prachi; Jayaraj, Gopal Gunanathan; Gargallo, Raimundo; Maiti, Souvik (Biochemistry, 2015)
The biological role of the existence of overlapping structures in RNA is possible yet remains very unexplored. G-Rich tracts of RNA form G-quadruplexes, while GC-rich sequences prefer stem-loop structures. The equilibrium between alternate structures within RNA may occur and influence its functionality. We tested the equilibrium between G-quadruplex and stem-loop structure in RNA and its effect on biological processes using pre-miRNA as a model system. Dicer enzyme recognizes canonical stem-loop structures in pre-miRNA to produce mature miRNAs. Deviation from stem-loop leads to deregulated mature miRNA levels, providing readout of the existence of an alternate structure per se G-quadruplex-mediated structural interference in miRNA maturation. In vitro analysis using beacon and Dicer cleavage assays indicated that mature miRNA levels depend on relative amounts of K+: and Mg2+ ions, suggesting an ion-dependent structural shift. Further in cellulo studies with and without TmPyP4 (RNA G-quadruplex destabilizer) demonstrated that miRNA biogenesis is modulated by G-quadruplex to stem-loop equilibrium in a subset of pre-miRNAs. Our combined analysis thus provides evidence of the formation of noncanonical G-quaciruplexes in competition with canonical stem-loop structure inside the cell and its effect on miRNA maturation in a comprehensive manner.

Tale of RNA G-quadruplex - Agarwala, Prachi; Pandey, Satyaprakash; Maiti, Souvik (Organic & Biomolecular Chemistry, 2015)
G-quadruplexes are non-canonical secondary structures found in guanine rich regions of DNA and RNA. Reports have indicated the wide occurrence of RNA G-quadruplexes across the transcriptome in various regions of mRNAs and non-coding RNAs. RNA G-quadruplexes have been implicated in playing an important role in translational regulation, mRNA processing events and maintenance of chromosomal end integrity. In this review, we summarize the structural and functional aspects of RNA G-quadruplexes with emphasis on recent progress to understand the protein/trans factors binding these motifs. With the revelation of the importance of these secondary structures as regulatory modules in biology, we have also evaluated the various advancements towards targeting these structures and the challenges associated with them. Apart from this, numerous potential applications of this secondary motif have also been discussed.

Targeting RNA G-Quadruplexes for potential therapeutic applications - Pandey,Satyaprakash; Agarwala, Prachi; Maiti,Souvik (Topics in Medicinal Chemistry, 2017)
RNA G-quadruplexes are non-canonical structures formed in G-rich regions of transcriptome. Considerable research points towards the potential role for these dynamic structures in various genes involved in multiple pathways. The ability of these structures to influence important biological processes has been demonstrated in few selected important genes and more recently in a global manner across the transcriptome. RNA G-quadruplexes are implicated in fundamental processes such as translational regulation, alternative splicing, mRNA transport and telomere homeostasis to name a few. The involvement of these structures in key biological processes makes them attractive targets for therapeutic interventions. Here we discuss the structural features of RNA G-quadruplex that make it more monomorphic to develop ligands unlike the polymorphic DNA G-quadruplexes. Furthermore, the role of RNA G-quadruplexes in important genes involved in diseases and disorders such as neurodegeneration, cancer and viral infections has been highlighted. A summary of ligands and their established roles in targeting RNA G-quadruplex structures has been discussed in context of important processes. Moreover, we highlight the need to develop ligands that are highly specific in targeting RNA G-quadruplexes, a new target to restore homeostasis in dysregulated conditions.